Challenges faced by secondary schools in the implementation of "No fee Schools Policy" in the Sekhukhune District of Limpopo Province - Mampuru, Motubatse William (University of Limpopo (Turfloop Campus), 2012)
The study was undertaken because the researcher was concerned about the denial of poor learners the right to education, as their parents could not afford to pay School Fees due to high unemployment and poverty in rural schools. The researcher noticed that schools sent learners home to collect school fees and also withheld learner reports until the required amount was paid. As a result, “Fee Exemption policy” was available to exempt poor parents from paying School Fees, but it was not effective because schools did not inform them to apply for this policy. As a result, poor learners decide to dropout. The government introduced “no-fee-schools” policy to end marginalisation of poor learners. Further, it appeared that School Allocations are little because rural schools have a shortage of school facilities and some of the facilities are too expensive.A purposive sampling strategy was used to select 3 public secondary schools as research sites and 26 respondents as a sample of the target population. Respondents consisted of 8 members; the principal, SGB member and 6 educators from School A; Nine (9) respondents; the principal, 2 SGB members and 6 educators from School B; the principal, 2 SGB members and 6 educators from School C. Twenty-six respondents were considered to be sufficient because my focus was not on representation. The respondents were considered to be key informants with required data. Interviews and document analysis were used as data collection methods. The researcher used semi-structured interviews because they are interactive, and they also give the respondents a voice associated with their perspectives and experiences. Document analysis was used to supplement data collected through interviews. The interviewees discovered that learners were denied the right to education, despite the departmental policies formulated to help poor learners and theirparents. Furthermore, “no-fee-schools” policy was formulated to enable poor students to access education, but it is problematic because School Allocation is not deposited to school accounts on time and does not cover all the school costs. The study recommends that poor learners should not be denied the right to education and that the departmental policy (viz., Fee Exemption Policy) should be monitored to ensure that marginalised learners benefit from this scheme. This policy should also be budgeted for so as to enable poor schools to purchase modern facilities to improve the quality of teaching and learning and employ extra educators so as to reduce the educator-learner ratios and so on.
Thesis (M.A.) --University of Limpopo, 2012
Keywords: No-fee school policy; Free education; 373.12; High Schools - South Africa; Policy making